2021
DOI: 10.5194/tc-15-897-2021
|View full text |Cite
|
Sign up to set email alerts
|

The cooling signature of basal crevasses in a hard-bedded region of the Greenland Ice Sheet

Abstract: Abstract. Temperature sensors installed in a grid of nine full-depth boreholes drilled in the southwestern ablation zone of the Greenland Ice Sheet recorded cooling in discrete sections of ice over time within the lowest third of the ice column in most boreholes. Rates of temperature change outpace cooling expected from vertical conduction alone. Additionally, observed temperature profiles deviate significantly from the site-average thermal profile that is shaped by all thermomechanical processes upstream. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…These sites are limited to western Greenland, where abundant surface meltwater is available (Iken and others, 1993; Harrington and others, 2015; Lüthi and others, 2015). Temperate ice thickness extending upward from the bed within an ice-stream shear margin could also result from upward heat transfer by meltwater infiltration through basal crevasses (McDowell and others, 2021), a process which is not included in our numerical model. This is a different mechanism than suggested by previous studies, which have indicated the possibility of significant temperate ice from strain heating.…”
Section: Discussionmentioning
confidence: 99%
“…These sites are limited to western Greenland, where abundant surface meltwater is available (Iken and others, 1993; Harrington and others, 2015; Lüthi and others, 2015). Temperate ice thickness extending upward from the bed within an ice-stream shear margin could also result from upward heat transfer by meltwater infiltration through basal crevasses (McDowell and others, 2021), a process which is not included in our numerical model. This is a different mechanism than suggested by previous studies, which have indicated the possibility of significant temperate ice from strain heating.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of water-filled basal crevasses can locally modify the thermal profile of the ice sheet (Luckman and others, 2012) and is a potential explanation of the spatially-varying temperate ice layer. The thermal structure of basal crevassing, which is similar to that of dykes in rock (Daniels and others, 2014), has been modelled in several studies (Jarvis and Clarke, 1974; McDowell and others, 2021). Their approach recognises that water-filled basal crevasses in sub-temperate ice propagate on a short timescale, followed by rapid refreezing of water inside the crack.…”
Section: Discussionmentioning
confidence: 99%
“…See Figure 1 Overall, 61 of the 85 profiles were available as tabulated temperature measurements (Heuberger, 1954;Classen, 1977;Stauffer and Oeschger, 1979;Clarke et al, 1987;Thomsen et al, 1991;Iken et al, 1993;Hansson, 1994;Cuffey et al, 1995;Thomsen et al, 1996;Cuffey and Clow, 1997;Dahl-Jensen et al, 1998;Fischer et al, 1998;Lüthi et al, 2002;Kinnard et al, 2006;Buchardt and Dahl-Jensen, 2007;Kinnard et al, 2008;Lemark and Dahl-Jensen, 2010;Rasmussen et al, 2013;Ryser et al, 2014;Harrington et al, 2015;Hills et al, 2017;Zekollari et al, 2017;Doyle et al, 2018b;Hubbard et al, 2021a;Harper and Meierbachtol, 2021;Law et al, 2021). The remaining 24 profiles were digitized from figures (Hansen and Landauer, 1958;Davis, 1967;Paterson, 1968;Classen, 1977;Paterson et al, 1977;Colbeck and Gow, 1979;Gundestrup and Hansen, 1984;Blatter and Kappenberger, 1988;Gundestrup et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…This thermal disturbance of hot-water drilling often requires many months to fully dissipate, as the latent energy released by the refreezing borehole warms surrounding ice. Empirical cooling curves of temperature measurements collected multiple times post drilling can usually constrain this thermal disturbance effect to better than ±0.1°C (Humphrey and Echelmeyer, 1990;Ryser et al, 2014;McDowell et al, 2021).…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation